Integrating Local Wisdom into Islamic Education Curriculum to Strengthen Religious Moderation: Lessons From Madurese Socio-Religious Culture - Helmi Fuad; Mufiqur Rahman; Ali Ridho (Fakultas Agama Islam Universitas Billfath, 2026)
This study aims to examine how the integration of local wisdom into the Islamic education curriculum can strengthen religious moderation in school settings. Using a qualitative approach with a socio-cultural perspective, data were collected through in-depth interviews, observation, document analysis, and focus group discussions involving teachers, school leaders, and students. The findings show that religious moderation can be effectively strengthened when local wisdom is systematically integrated into curriculum content, learning practices, school culture, and institutional policies. Cultural traditions, community values, and local religious practices function as contextual learning resources that help students understand moderation as a lived experience rather than an abstract concept. Teacher role modeling, dialogical learning, and habituation through daily activities also play a significant role in shaping tolerant and balanced attitudes. The study contributed a local wisdom–based model consisting of curriculum integration, teacher example, school culture, and institutional support as key components for strengthening religious moderation in Islamic education.